2015
DOI: 10.1007/s12070-015-0859-y
|View full text |Cite
|
Sign up to set email alerts
|

Electronystagmography a Very Useful Diagnostic Tool in Cases of Vertigo

Abstract: A significant number of patients seen in otorhinolaryngology have symptoms of vestibular dysfunction. Examination of vestibulo-ocular reflex has been and still is the principal method of evaluating vestibular functions. Electronystagmography (ENG) has been the gold standard to test the vestibular functions. The present study aims to evaluate the utility of ENG in diagnosing the etiology of vertigo. Total of 50 patients of either sex presenting with vertigo underwent ENG after a detailed history according to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 7 publications
1
7
0
2
Order By: Relevance
“…10 In study done by Gupta and Mundra abnormal nystagmus on positional test for three positions was seen in 44% of patients. 12 In our study abnormal smooth pursuit nystagmus on pendulum test was found in 6 patients (10%). All these cases were further evaluated by CT/MRI and referred to higher center.…”
Section: Presenting Complaintsmentioning
confidence: 44%
“…10 In study done by Gupta and Mundra abnormal nystagmus on positional test for three positions was seen in 44% of patients. 12 In our study abnormal smooth pursuit nystagmus on pendulum test was found in 6 patients (10%). All these cases were further evaluated by CT/MRI and referred to higher center.…”
Section: Presenting Complaintsmentioning
confidence: 44%
“…Diagnostic tests include an MRI of the head, with and without contrast, to determine central nervous system or peripheral or inner ear disorders (National Clearinghouse Guidelines, 2014). Electronystagmography can determine the central versus peripheral etiology of nystagmus (Gupta & Mundra, 2015). An ENG measures function of the oculomotor and vestibular systems via positional testing and stimulation of the vestibular system.…”
Section: Discussionmentioning
confidence: 99%
“…Their vestibular function was tested by Electronystagmography test, which is the gold standard test to detect the vestibular functions (11).…”
Section: Exclusion Criteriamentioning
confidence: 99%